Analisis Transmisi Kebijakan Moneter Syariah Terhadap Kinerja UMKM - Lailan Safina Hasibuan; Julita Julita; Andri Soemitra (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2023)
Sharia monetary policy is an approach carried out by Islamic-based financial institutions that regulate and carry out monetary policy. All policies implemented must be based on sharia principles, in which sharia principles clearly prohibit usury (interest), excessive speculation and other transactions that are contrary to the principles of justice. This study aims to analyze the transmission of Islamic monetary policy to the performance of MSMEs in Medan City. This study uses a descriptive approach. With observation and interview techniques given to MSME actors in the city of Medan. Based on the research results, it can be concluded that the transmission of sharia monetary policy has on the performance of MSMEs. The transmission of sharia monetary policy has boosted MSME business performance by providing better access to capital, business assistance and consulting and better financial management.